2020
DOI: 10.3389/fonc.2019.01423
|View full text |Cite
|
Sign up to set email alerts
|

PELP1 Suppression Inhibits Gastric Cancer Through Downregulation of c-Src-PI3K-ERK Pathway

Abstract: Background: Proline-, glutamic acid-, and leucine-rich protein 1 (PELP1), a co-activator of estrogen receptors alpha, was confirmed to be directly associated with the oncogenic process of multiple cancers, especially hormone-dependent cancers. The purpose of our research was to explore the biological function, clinical significance, and therapeutic targeted value of PELP1 in gastric cancer (GC). Methods: The expression status of PELP1 in GC cell lines or tissues was analyzed through bioinformatics data mining.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The Src/PI3K/ERK signaling pathway has been intricately associated with cell proliferation [57] . Inhibition of phosphorylated ERK1/2/MAPK, known for its role in cell proliferation, has been linked to hyperthermia-induced NTDs [58] .…”
Section: Discussionmentioning
confidence: 99%
“…The Src/PI3K/ERK signaling pathway has been intricately associated with cell proliferation [57] . Inhibition of phosphorylated ERK1/2/MAPK, known for its role in cell proliferation, has been linked to hyperthermia-induced NTDs [58] .…”
Section: Discussionmentioning
confidence: 99%
“…FOXO-regulated genes mainly include those that regulate the cell cycle and cellular death, autophagy, metabolism, and antioxidative processes. FOXO, as a switch that regulates a large class of functional genes, is an important research object in medical biology and life science [ 27 , 28 ]. Cell lines that stably express FOXO can provide a reliable platform to study this family.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found Src/PI3K/Akt signaling pathway activation is responsible for the GC tumorigenesis (15,16), furthermore, the western-blot was applied to study the roles of CEACAM6 in proteins of Src/PI3K signaling pathway, with the results showing that CEACEM6 over expression can up regulate the expression of p-Src, p-PI3K, p-Akt and MMP9 proteins in the AGS and MKN-45 cells, however, when the Src was inhibited, the down regulation of p-PI3K, p-Akt and MMP9 cannot be recovered by CEACAM6 (Figure 3D). It was speculated that CEACAM6 can accelerate the GC tumorigenesis and progression by Src/PI3K/ Akt signaling pathway (Figure 3E).…”
Section: Ceacam6 Promoted the Invasive Metastatic And Proliferative Ability Of Gc Cellsmentioning
confidence: 99%